Application of cobalt based polyoxometalates and zirconia nanocomposite for electrocatalytic water splitting - Wai, Jia Min (Nanyang Technological University, 2020)
Generating a sustainable source of hydrogen energy has been on the radar of many developed countries as of late. One promising method is the usage of transition metals as a water oxidation catalyst to speed up the rate of the water-splitting reaction. However, the high cost associated with transition metals prevents them from being an optimal choice. On the other hand, polyoxometalates (POM), a complex molecule is also garnering massive attention due to their excellent water splitting capabilities. However, one major drawback of these molecules is the lack of an immobile support which in turn limits their effective catalytic surface area extensively. Hence, this report seeks to design a novel CoPW9 POM-Zirconia Nanocomposite with Zirconia as the solid support for the CoPW9 POM to improve the water splitting capabilities as compared to original CoPW9 POM. A series of tests, namely Field Emission Scanning Electron Microscopy (FESEM), Electron Dispersive X-ray Spectroscopy (EDX), XRay Powder Diffraction (XRD), Fourier Transform Infrared Spectroscopy (FTIR), Thermal Gravimetric Analysis (TGA) and Ultraviolet-Visible Spectroscopy (UV-VIS) was conducted to characterise this novel nanocomposite. To determine if the water splitting capabilities of the nanocomposite is superior to that of the original CoPW9 POM, linear sweep voltammetry tests were run on three different compositions of the electrocatalyst. The result that came through was that the electrocatalyst that had the novel nanocomposite and carbon powder in the ratio of 5:5 yielded the best water splitting effect.